Policies for the Implementation of Teaching and Learning Activities in the Context of Handling the Pandemic Covid-19 in Padang Panjang City During the Phase I Implementation of Restrictions on Micro-Based Community Activities (July 2021) - Rico Candra; Roni Ekha Putera; Ria Ariany (Fakultas Ilmu Sosial dan Ilmu Pendidikan Universitas Tadulako, 2022)
Since the Covid-19 virus arrived in Indonesia in early 2020, it has altered the order of life in the country, including the order of education. COVID-19 affects a variety of community groups, including students. Because the Covid-19 virus spreads through human-to-human contact, the process of learning and teaching activities in schools that were initially carried out face-to-face were immediately changed to methods other than face-to-face. Padang Panjang City is one of the small towns in West Sumatra Province that has been affected by the Covid-19 virus's spread. Due to the high spread of the Covid-19 virus in the City of Padang Panjang in mid-2021, the Padang Panjang City Government has participated in implementing the policy of Enforcement of Community Activity Restrictions (micro-based), which has an impact on teaching and learning activities that are also carried out online. 100% actually work from home. However, there are still violations committed by educational institutions in the City of Padang Panjang in the implementation of the ECAR (micro-based) policy, for example, teaching and learning activities are still carried out face-to-face. The research method used in this study is qualitative descriptive research.